2017
DOI: 10.1016/j.msea.2017.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Growth twins in high stacking fault energy metals: Microstructure, texture and twinning

Abstract: This work explores the formation of twin boundaries in high stacking fault energy metals (SFE > 125 mJ/m 2 ) by synthesizing thick films (> 10 μm) of Al, Al-5.3wt.%Mg, and Ni using magnetron sputtering. We report the observation of twin boundaries that are inclined with respect to the film growth direction across the entire thickness of the films. The formation of these inclined twin boundaries results in localized changes in the texture of the columnar grains.Microstructural analysis revealed that the fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…To understand the changes in special GBs among the three samples, one can look at a simplified model for Σ3 boundaries only. In Al alloys, a previous study demonstrated that sputtering rates ≥7 nm s −1 led to high fractions of twinned grains (46–70%), which agrees with the observed high fraction of special boundaries for sample C. This increase in twin boundaries was attributed to both the high sputtering rate and the decrease in GB mobility due to stress relaxation during film growth, [ 15 ] present during interrupted sputtering, making twins and special GBs more energetically favorable. [ 23,34 ] In samples A and B, the changes in sputtering rate did not yield a significant change in the GB fraction, which is likely due to the probability ( ρ) of twin boundary nucleation during film growth and its relationship to the deposition flux, where flux is proportional to the sputtering rate.…”
Section: Figuresupporting
confidence: 80%
See 4 more Smart Citations
“…To understand the changes in special GBs among the three samples, one can look at a simplified model for Σ3 boundaries only. In Al alloys, a previous study demonstrated that sputtering rates ≥7 nm s −1 led to high fractions of twinned grains (46–70%), which agrees with the observed high fraction of special boundaries for sample C. This increase in twin boundaries was attributed to both the high sputtering rate and the decrease in GB mobility due to stress relaxation during film growth, [ 15 ] present during interrupted sputtering, making twins and special GBs more energetically favorable. [ 23,34 ] In samples A and B, the changes in sputtering rate did not yield a significant change in the GB fraction, which is likely due to the probability ( ρ) of twin boundary nucleation during film growth and its relationship to the deposition flux, where flux is proportional to the sputtering rate.…”
Section: Figuresupporting
confidence: 80%
“…[ 14 ] For sputtering in particular, a previous study demonstrated that the fraction of twin boundaries in Ni and Al could be modified through the use of different sputtering rates. [ 15 ] Furthermore, a sputtered 5xxx series Al–Mg alloy demonstrated both higher fractions of low Σ (≤29) GBs and improved resistance to sensitization compared with conventional materials. [ 9 ] In this study, we go several steps further by focusing on tailoring the fraction of special GBs in a complex alloy as well as directly correlating the GB fraction to corrosion morphology.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations